The Conceptual Framework Of Parental Abuse Through Neglect - Manser, Messaouda (University of Eloued جامعة الوادي, 2024)
Abstract: Abuse by neglect is defined as the failure of the parents to provide the basic and developmental needs of the child in the areas of health, education, emotional development, nutrition, housing, in the context of their ability to do so, and it is considered one of the modern social problems, as any child suffers from it, regardless of his social or economic level. and for this has been done Taking the concept is theoretically of this type of abuse with the righteousness of its danger and its repercussions on the children. It occurs as a result of an interaction between a group of factors that leads to its interaction to results and effects that lead to harm to the child in his physical and psychological development. الملخص: تعرف الإساءة بالإهمال على أنها إخفاق الوالدين في توفير الحاجيات الأساسية والنمائية للطفل في مجالات الصحة ، التعليم ،التطور العاطفي، التغذية، المسكن ، في سياق قدرتهم على ذلك، وتعد من اﻟﻤشـﻜﻼت اﻻﺟﺘﻤﺎﻋﻴﺔ الحديثة، حيث ﻳﻌﺎﻧﻲ ﻣﻨﻬـﺎ أي طفل ﺑﺼﺮف النظر عن مستواه اﻻجتماعي او اﻻﻗﺘﺼﺎدي او العلمي، ولهذا تم تناول الاطار المفاهيمي نظريا لهذ النوع من الاساءة برصدعوامل خطرها وتداعياتها على الابناء. فهي تحدث نتيجة تفاعل بين مجموعة من العوامل ، تؤدي محصلة تفاعلها إلى نتائج واثار تؤدي إلى حدوث أذى للطفل في تطوره الجسدي، والنفسي.
Monitoring Its Risk Factors And Repercussions On The Child
Keywords: Abuse; Neglect; Child; factors; Effects; الاساءة; الاهمال; التداعيات